Social Interaction between Juvenile Inmates and Adult Prisoners: A Study at the Class I State Detention Center of Tanjungpinang - Desmayeti Arfa; Endri Bagus Prastiyo; Alfi Husni; Desrian Effendi; Rianto; Yulius Hermawan; Nik Nur Azizah Nik Halman (University of Muhammadiyah Malang, 2026)
The dynamics of social life within detention centers (RUTAN) often give rise to unique patterns of relationships, where interactions among inmates may generate various forms of social behavior, both positive and negative. In this context, it is essential to understand how social interaction processes within a closed environment can influence the social and emotional development of inmates. This study aims to explain how social interaction factors among juvenile inmates affect their socio-emotional development during their confinement at the Class I State Detention Center of Tanjungpinang. This research employs a descriptive qualitative method, with data collected through observation, interviews, triangulation, and documentation, and analyzed using social interaction theory involving factors such as imitation, suggestion, and identification. The findings indicate that social interactions within the detention environment tend to be deviant in nature, where juvenile inmates who interact with adult inmates are likely to imitate, be influenced by, and identify with negative behaviors from their surroundings, which in turn contributes to violent behavior, the internalization of negative symbolic meanings, and a tendency toward recidivism. These findings highlight how patterns of social interaction shape the behavior and socio-emotional development of juvenile inmates within the detention setting.